Metabolome alterations: a tool to assess efficacy in clinical trials for neuronopathic lysosomal disorders? - Giugliani, Roberto; Baldo, Guilherme (Biotarget; Vol 1 (September 2017): Biotarget, 2017)
When setting a clinical trial, one of the main difficulties is to establish which measurements of treatment efficacy will be informative. Studies in animal models allow tissue extraction, for example, and therefore in situ quantification of molecule, a possibility that usually is not available in clinical studies. This is especially true when the disease studied is rare, because frequently little is known regarding the natural history of disease progression, being assessment of the brain function particularly difficult.